Netrin 1-Mediated Role of the Substantia Nigra Pars Compacta and Ventral Tegmental Area in the Guidance of the Medial Habenular Axons - Company, Verónica; Andreu-Cervera, Abraham; Madrigal, M. Pilar; Andrés, Belén; Almagro-García, Francisca; Chédotal, Alain; López-Bendito, Guillermina; Martinez, Salvador; Echevarría, Diego; Moreno-Bravo, Juan A.; Puelles, Eduardo (Frontiers in Cell and Developmental Biology, 2021)
The fasciculus retroflexus is an important fascicle that mediates reward-related behaviors and is associated with different psychiatric diseases. It is the main habenular efference and constitutes a link between forebrain regions, the midbrain and rostral hindbrain. The proper functional organization of habenular circuitry requires complex molecular programs to control the wiring of the habenula during development. However, the mechanisms guiding the habenular axons towards their targets remain mostly unknown. Here, we demonstrate the role of the mesodiencephalic dopaminergic neurons (Substantia Nigra pars compacta and Ventral Tegmental Area) as an intermediate target for the correct medial habenular axons navigation along the anteroposterior axis. These neuronal populations are distributed along the anteroposterior trajectory of these axons in the mes-diencephalic basal plate. Using in vitro and in vivo experiments, we determined that this navigation is the result of Netrin1 attraction generated by the mesodiencephalic dopaminergic neurons. This attraction is mediated by the receptor DCC, that is strongly expressed in the medial habenular axons. The increment in our knowledge on the fasciculus retroflexus trajectory guidance mechanisms opens the possibility to analyze if its alteration in mental health patients could account for some of their symptoms.